2008
DOI: 10.1111/j.1399-3054.2007.01043.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of two closely related β‐carbonic anhydrases from Chlamydomonas reinhardtii

Abstract: Aquatic photosynthetic organisms such as the green alga Chlamydomonas reinhardtii respond to low-CO(2) conditions by inducing a CO(2) concentrating mechanism (CCM). Important components of the CCM are the carbonic anhydrases (CAs), zinc metalloenzymes that catalyze the interconversion of CO(2) and HCO(-)(3). Six CAs have previously been identified in C. reinhardtii. Here, we identify and characterize two additional beta-type CAs. These two CAs are closely related beta-type CAs and have been designated as CAH7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 41 publications
2
63
1
1
Order By: Relevance
“…These results are confirmed by the companion article (Fang et al, 2012), including the activation of CAH1 and CAH4/ CAH5. As a notable difference to the observations of Ynalvez et al (2008) and Fang et al (2012), we found CAH3 slightly upregulated. In the cia5 mutant, Fang et al found that CAH5, the most highly upregulated CA gene in wild-type cells, is actually repressed.…”
Section: Carbonic Anhydrasescontrasting
confidence: 99%
See 1 more Smart Citation
“…These results are confirmed by the companion article (Fang et al, 2012), including the activation of CAH1 and CAH4/ CAH5. As a notable difference to the observations of Ynalvez et al (2008) and Fang et al (2012), we found CAH3 slightly upregulated. In the cia5 mutant, Fang et al found that CAH5, the most highly upregulated CA gene in wild-type cells, is actually repressed.…”
Section: Carbonic Anhydrasescontrasting
confidence: 99%
“…Four of the nine a-and b-CA genes (CAH1, CAH4/CAH5, and CAH7) were activated (twofold or more) (Figure 2; see Supplemental Data Sets 2 and 7 online) and none were repressed significantly (FDR # 0.01). Transcripts encoding CAH1, an a-type, periplasmic CA and CAH4/CAH5, recently duplicated, mitochondrial, b-type CAs were induced by over 2 9 (512-fold), similar to RT-PCR observations by Ynalvez et al (2008). These results are confirmed by the companion article (Fang et al, 2012), including the activation of CAH1 and CAH4/ CAH5.…”
Section: Carbonic Anhydrasessupporting
confidence: 77%
“…The multiplicity of fungal CA-isoforms leads to the assumption that the proteins are involved in various processes and are targeted to diVerent cellular compartments, as it has been described in plants, algae and animals (Hewett-Emmett and Tashian 1996; Moroney et al 2001;Supuran 2008;Ynalvez et al 2008). Because of the high degree of sequence identity, these functional speciWcations and the subcellular localization events are thought to be quite recent (Hewett-Emmett and Tashian 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In the freshwater chlorophyte, Chlamydomonas reinhardtii, chloroplastic CAs, a pyrenoidal component including low-CO 2 -inducible protein (LCI) B/C, and the membrane transporter, LCI1, are known to facilitate the CCM (14)(15)(16)(17). Additionally, the role of extracellular CAs (CA ext ) in CCM has been controversial in the study of green algae (18).…”
mentioning
confidence: 99%